A Framework for Conservation Construction Plan Model (CCPM). (2017) - Wang, Anqi; Chan, Edwin; Yeung, Stanley
Abstract: Land development and construction activities influence adversely on the ecological environment, in most circumstances. However, the growing awareness of sustainable development and peoples' willingness to pay for natural landscapes enable developers to gain rather than lose profit from land conservation activities. Therefore, confronting the conflict of land development and land conservation, it is important to understand the relationships between construction plan and its conservation implications as well as economic benefits. This study proposed a framework of conservation construction plan model (CCPM), and three parts of the model framework were represented. Literatures of landscape features and their relationship with housing prices were reviewed, as the basis of model design. This study contribution to the body of knowledge with a set of factors, related to land use structure, landscape environment, conservation value, residential development characteristics, construction density, housing price, etc. which were identified and considered in the model. It also contribute the CCPM to show construction plan scenarios with different land use structures and patterns and to compare the scenarios with changes in economic and environment values, etc. The model framework would contribute to creative construction plans, as a supporting tool for making scientific decisions, preserving land ecological value and maximizing the integrated utility of land resources.